Myth or history? Ancient Greek mythology in Paparrigopoulos’ History of the Hellenic nation: controversies, influences and implications - Konaris, Michael D. (The Historical Review/La Revue Historique, 2020)
This article examines the treatment of Greek mythology in Paparrigopoulos’ History of the Hellenic nation (1860–1874) in the light of contemporary Western European historiography. The interpretation of Greek myths was highly contested among nineteenth-century scholars: could myths be used as historical sources or were they to be dismissed as figments of imagination devoid of historical value? did they express in allegorical form sublime religious doctrines that anticipated Christianity, or did they attest to the Greeks’ puerile notions about the gods? The article investigates how Paparrigopoulos positioned himself with respect to these questions, which had major consequences for one’s view of early Greek history and the relation between ancient Greek culture and christianity, and his stance towards traditional and novel methods of myth interpretation such as euhemerism, symbolism, indo-european comparative mythology and others. it explores how Paparrigopoulos’ approach differs from those encountered in earlier modern Greek historiography, laying stress on his attempt to study Greek myths “scientifically” on the model of Grote and the implications this had. in addition, the article considers Paparrigopoulos’ wider account of ancient Greek religion’s relation to Christianity and how this affected the thesis of the continuity of Greek history.